2019
DOI: 10.3390/polym11121942
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Properties of Hybrid Coffee-Cellulose Aerogels from Spent Coffee Grounds

Abstract: A fully biodegradable hybrid coffee-cotton aerogel has been successfully developed from spent coffee grounds, 100% cotton fiber and polyvinyl alcohol (PVA) flakes via environmental friendly processes. The cotton fibers in coffee aerogel help to maintain the structure and improve the overall properties of the new hybrid coffee-cotton aerogel. The results show that increasing the concentration of fibers, while keeping the concentration of spent coffee grounds constant, the sinking of coffee ground particles in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…For a 0.0588 g CP-dc, it could withstand a 200 g weight in its longitudinal direction without collapsing (Figure 5b), which proved its excellent compression resistance. This lightweight but high-strength characteristic was also superior to previously reported aerogels, e.g., 1-CNF aerogel, 28 2-CNF aerogel, 29 3- cellulose nanocrystal aerogel, 30 4-CNF aerogel modified via CVD of methyltrimethoxysilane, 31 5-TEMPO-CNF aerogel, 32 6-cellulose nanocrystal aerogel, 33 7-CNF aerogel, 34 8-CNF aerogel, 35 9-cross-linked CNF aerogel, 36 10-CNF/graphene oxide/sepiolite nanorod aerogel, 37 11-CNFs/AgNW@Fe 3 O 4 sponge, 38 12-cellulose/poly(vinyl alcohol) (PVA) aerogel, 39 13-CNFs/AgNWs sponge, 17 14-cellulose/silica aerogel, 40 and 15-coffee/cellulose/PVA aerogel 41 (Figure 5c and Table S2).…”
Section: Resultsmentioning
confidence: 93%
“…For a 0.0588 g CP-dc, it could withstand a 200 g weight in its longitudinal direction without collapsing (Figure 5b), which proved its excellent compression resistance. This lightweight but high-strength characteristic was also superior to previously reported aerogels, e.g., 1-CNF aerogel, 28 2-CNF aerogel, 29 3- cellulose nanocrystal aerogel, 30 4-CNF aerogel modified via CVD of methyltrimethoxysilane, 31 5-TEMPO-CNF aerogel, 32 6-cellulose nanocrystal aerogel, 33 7-CNF aerogel, 34 8-CNF aerogel, 35 9-cross-linked CNF aerogel, 36 10-CNF/graphene oxide/sepiolite nanorod aerogel, 37 11-CNFs/AgNW@Fe 3 O 4 sponge, 38 12-cellulose/poly(vinyl alcohol) (PVA) aerogel, 39 13-CNFs/AgNWs sponge, 17 14-cellulose/silica aerogel, 40 and 15-coffee/cellulose/PVA aerogel 41 (Figure 5c and Table S2).…”
Section: Resultsmentioning
confidence: 93%
“…[ 7 ] After being coated with PDMS, PDMS/PCA sample exhibited two characteristic peaks at 1100 and 800 cm ‐1 , corresponding to vibrational stretching of Si–C and –CH 3 in siloxane compound, respectively. [ 21,22 ] Moreover, the intensity of characteristic peaks between 2950 and 2970 cm ‐1 increased significantly in the spectrum of PDMS/PCA. It can be explained by the addition of –CH 3 from –O–Si–(CH 3 ) 3 of PDMS, displacing –OH groups, therefore, enhancing the hydrophobicity of PDMS/PCA.…”
Section: Resultsmentioning
confidence: 99%
“…The fitting results of the experimental data (table 2) show that the calculated R 2 value from the pseudo‐second‐order model reaches 0.99 which higher than that of the other ones. [ 21 ] This result showed that the adsorption behavior of PDMS/PCA for both cooking and lubricating oils obeyed to pseudo‐second‐order model, considering the chemical sorption phenomenon. [ 10 ] Furthermore, the adsorption stability of the PDMS/PCA for two investigated oil was evaluated for 5 cycles of adsorption ‐ compression as presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have considered hybridizing different materials with cellulose fibers to produce composite aerogels to improve properties, for instance, cellulose nanocrystals and red mud 47 to improve magnetic conductivity, surface area or spent coffee ground and cotton pads 41 to improve oil adsorption capacity and compressive Young's modulus. Even though the properties of hybrid aerogels normally show significant improvement over non-hybrid aerogels, there is still a gap in the fundamental and theoretical basis of the tunability of interactions between cellulose and other materials.…”
Section: Current Development Of Aerogels From Lignocellulosic Materialsmentioning
confidence: 99%